METHODS OF DEVELOPING INFORMATION CULTURE USING MEDIA TOOLS IN THE EDUCATIONAL PROCESS - Ergasheva Shahnoza Mavlonboyevna (Bright Mind Publishing, 2025)
This article explores the use of information technologies and multimedia tools in designing and implementing video-based FAQ (Frequently Asked Questions) solutions within employee and user onboarding processes. The study emphasizes how interactive video tutorials, motion graphics, and AI-driven chat interfaces can optimize knowledge transfer, reduce onboarding time, and enhance user engagement. The integration of cloud-based learning management systems (LMS), streaming technologies, and responsive multimedia design enables organizations to deliver consistent and personalized onboarding experiences. By combining instructional design principles with ICT frameworks, video-FAQ systems create an adaptive learning environment that supports both visual and auditory learners. The paper also analyzes user analytics, feedback loops, and accessibility parameters to assess system effectiveness. The findings demonstrate that multimedia-enhanced onboarding significantly improves comprehension, retention, and overall user satisfaction, leading to more efficient digital transformation and workforce productivity.
Keywords: Onboarding, information technology, multimedia tools, video-FAQ, learning management system, AI chatbot, instructional design, interactive learning, user engagement, digital transformation, employee training.